(411) Regional Planning التخطيط الإقليمي - Tinbergen, J. (معهد التخطيط القومى, 2024)
The study entitled “Regional Planning on the Basis of Projects and Industrial Complex Analysis” examines the theoretical and methodological foundations of regional planning within the broader framework of economic development and planning. The importance of the study lies in the argument that economic development cannot be achieved merely through broad macroeconomic objectives; rather, it depends significantly on the selection and geographical distribution of investment projects in ways that ensure efficient allocation of scarce resources and reduce regional disparities. The study proposes an analytical framework linking project selection with both national and regional development objectives. The research aims to establish a project-based planning approach in which projects are treated as fundamental planning units, taking into account their contribution to policy goals and their requirements for scarce resources. The analysis distinguishes between geographically transferable and non-transferable projects and examines how such distinctions influence regional investment decisions. The study argues that regional planning should not focus exclusively on aggregate economic efficiency but should also incorporate spatial equity and the reduction of developmental imbalances among regions. The study further reviews alternative regional policy models, beginning with passive policies that allow growth patterns to evolve naturally across regions and extending to active policies designed to support economically disadvantaged areas through targeted investment allocation. The findings suggest that such policies may require sacrificing certain short-term national gains in order to achieve broader social and developmental objectives. The research also discusses industrial complex analysis as a supporting instrument in planning processes. This approach is used to determine optimal project sizes, suitable locations, and efficient combinations of industrial activities through mathematical programming methods. The study concludes that effective planning requires integrating quantitative analytical methods with regional, social, and long-term developmental considerations.